Kewenangan Kepolisian Daerah Bali dalam Penegakan Hukum Terhadap Aksi Unjuk Rasa yang Anarkis - I Nyoman Budiantara; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Warmadewa Press, 2021)
Freedom of expression in public is the right of every citizen which is protected by law. There are several principles that must be followed in expressing opinions in public, namely the principle of balancing rights and obligations, deliberation and consensus, legal certainty and justice, proportionality, and benefits. However, the fact is that demonstrations are often carried out in an anarchic manner. The purpose of this study is to determine the authority of the Bali police in law enforcement against anarchic demonstrations, and to find out the obstacles faced by the Balinese police in dealing with demonstrations. This study uses empirical legal research because of the gap between theory and reality. The results of the research that the authority of the Bali Regional Police in law enforcement against anarchist demonstrations refers to Law/8/1998 and the National Police Chief Regulation No. Pol. 16 of 2006, as well as Protap No. PROTAP/1/X/2010. Barriers to the Bali Police in dealing with anarchic demonstrations are divided into internal inhibiting factors such as knowledge, emotions, and delays in information. The external such as no permission to protest, influenced by alcohol. To the public, to always comply with the laws and regulations in terms of demonstrations.